Structure of the Western Jaz Murian Forearc Basin, Southeast Iran, Revealed by Autocorrelation and Polarization Analysis of Teleseismic P and S Waves. Issue 4 (1st April 2022) - Lan, Haiqiang; Chen, Ling; Chevrot, Sebastien; Talebian, Morteza; Wang, Xu; Gao, Yifan; Zhang, Jianyong; Wu, Zimu; Shokati, Mehdi; Jiang, Mingming; Ai, Yinshuang; Hou, Guangbing; et al.
Abstract: The Jaz Murian Basin in Southeast Iran is a forearc basin that sits on top of the western Makran subduction zone. A recent seismic deployment inside the western Jaz Murian Basin documents extremely strong reverberations between the free surface and the top of the basement. These strong multiples, which hamper studies of deeper structures, carry precious information on the structure of the basin. Here we combine three independent measurements, including teleseismic P/S‐wave coda autocorrelations, P‐wave polarization analysis and receiver functions, to image the architecture of the western Jaz Murian Basin. The S‐wave velocity structure beneath each station is constrained by teleseismic P‐wave polarization analysis and a simple grid search method. In addition, both P‐ and S‐wave reflections are extracted to measure the Poisson's ratio and the thickness of sediments, in addition to P‐ and/or S‐wave velocities. We find that the sedimentary cover has an average thickness of ∼3 km with very low S‐wave velocities around 1.2 km/s. The estimated Vp/Vs ratios are relatively high between 2.23 and 2.52, suggesting that the western Jaz Murian Basin contains unconsolidated recently deposited sediments. Plain Language Summary: Passive imaging studies usually suffer from a limited spatial resolution owing to lower frequency content and sparser acquisition compared to active source seismic experiments. On the other hand, the former are easier to perform for a fraction of the cost of the latter. In this study, we exploit teleseismic body waves recorded by our recently deployed temporary array in the western Jaz Murian forearc basin, southeast Iran. Our results reveal the detailed structure of the western Jaz Murian sedimentary basin, mostly filled with unconsolidated sediments, possibly originating from lake deposition. Key Points: We extract energetic P‐ and S‐wave reflections from the coda of teleseismic P and S waves We combine these reflections with measurements of P wave polarization to resolve the structure of the western Jaz Murian sedimentary basin The nature of the sediments inside the Jaz Murian Basin and of the basement provides insight into the recent tectonic regime in that region